2009
DOI: 10.1037/a0016953
|View full text |Cite
|
Sign up to set email alerts
|

A multitrait (ADHD–IN, ADHD–HI, ODD toward adults, academic and social competence) by multisource (mothers and fathers) evaluation of the invariance and convergent/discriminant validity of the Child and Adolescent Disruptive Behavior Inventory with Thai adolescents.

Abstract: Confirmatory factor analysis was used with a multitrait (attention-deficit/hyperactivity disorder-inattention, attention-deficit/hyperactivity disorder-hyperactivity/impulsivity, oppositional defiant disorder toward adults, academic competence, and social competence) by multisource (mothers and fathers) matrix to test the invariance and convergent/discriminant validity of the 5-factor model between mothers' and fathers' ratings of Thai adolescents (Year 1: n = 872; Year 2: n = 903; Year 3: n = 700; Year 4: n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Academic and social impairment items are reversed keyed so higher scores represented higher levels of academic and social impairment. Earlier studies (Burns et al., , ; Khadka & Burns, ) provide support for the reliability and validity of the scale's ADHD‐IN, ADHD‐HI, ODD, academic and social impairment scores.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Academic and social impairment items are reversed keyed so higher scores represented higher levels of academic and social impairment. Earlier studies (Burns et al., , ; Khadka & Burns, ) provide support for the reliability and validity of the scale's ADHD‐IN, ADHD‐HI, ODD, academic and social impairment scores.…”
Section: Methodsmentioning
confidence: 83%
“…Return rates were 49% for Brazilian children, 43% for US children, 71% for Thai children, and 85% for Thai adolescents. More detailed descriptions of the four samples appear in Burns et al., ; Burns, Desmul, Walsh, Silpakit, & Ussahawanitchakit, ).…”
Section: Methodsmentioning
confidence: 99%
“…reports across children in different countries (Thailand, Brazil, North America, Australia, Malaysia) (Burns, et al, 2008;Burns, Desmul, Walsh, Silpakit, & Ussahawanitchakit, 2009) and across ages 9 to 16 (Sterba, et al, 2010). Measurement invariance across sex has also been demonstrated for American and Malaysian children (and boys scored higher than girls) (Burns, Walsh, Gomez, & Hafetz, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…In terms of stability, Boylan, Vaillancourt, & Szatmari (2012) measured ODD symptoms in a sample of 932 four and five year olds five times over eight years and found that baseline ODD symptoms had significant correlations of .61, .51, .53, and .43 with ODD symptoms 2, 4, 6, and 8 years later, respectively (see also Lavigne et al, 2001; Whelan, Stringaris, Maughan, & Barker, 2013). In terms of consistency across settings, although correlations between different sources within the same settings (mothers with fathers; teachers with teachers) tend to be higher than between sources across different settings (parents with teachers), correlations between home and school are usually significant (e.g., Bernad, Servera, Grases, Collado, & Burns, 2014; Burns et al, 2008; Burns, Desmul, Walsh, Silpakit, & Ussahawanitchaki, 2009; Burns, Walsh, et al, 2013). …”
mentioning
confidence: 99%